Age-dependent variations in proteomic characteristics of spermatozoa in Simmental bull - Satrio, Faisal Amri; Karja, Ni Wayan Kurniani; Setiadi, Mohamad Agus; Kaiin, Ekayanti Mulyawati; Pardede, Berlin Pandapotan; Purwantara, Bambang (Frontiers in Veterinary Science, 2024)
Increasing the age of bulls results in a decrease in reproductive function, including a reduction in sperm quality, which plays a vital role in determining the fertility of bulls. Through a proteomic approach, this research aims to analyze the influence of age factors on various proteomes contained in bull sperm. Frozen semen samples from Simmental Bulls were categorized into three age groups: two, four, and ≥10 years old. Subsequently, the post-thaw sperm cells obtained were separated based on molecular weight using 1D-SDS-PAGE. Peptides extracted from the bands produced in each age group were subjected to LC-MS/MS analysis. A total of 72 protein types were identified, with 45 being detected in the 4-year-old group and 41 expressed in both the 2 and ≥10-year-old groups. The results provided insights into proteins' role in sperm metabolism across all age groups. Specifically, the 2-year-old group exhibited the expression of proteins associated with acrosome assembly and spermatid development (SPACA1). In contrast, those in the 4-year-old group were linked to motility (PEBP4) and sperm decapacitation factor (PEBP1). Proteins expressed in the 2 and -year-old groups were discovered to be involved in fertilization processes (TEX101). In contrast, the ≥10-year-old age group was associated with hyperactive movement related to capacitation (Tubulin). In conclusion, age influenced the differences observed in the proteomic profile of post-thaw Simmental bull sperm using the 1D-SDS-PAGE tandem LC-MS/MS approach.